2011
DOI: 10.1111/j.1532-5415.2011.03450.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Medications and Risk of Falls, Syncope, and Related Adverse Events: Meta-Analysis of Randomized Controlled Trials

Abstract: Background Conflicting evidence exists on whether cholinesterase inhibitors and memantine increase the risk of falls, syncope, and related events, defined as fracture and accidental injury. Objectives To evaluate the effect of cholinesterase inhibitors and memantine on the risk of falls, syncope, and related events Design, Setting, Participants, and Intervention Meta-analysis of 54 placebo-controlled randomized trials and extension studies of cholinesterase inhibitors and memantine that reported falls, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 86 publications
(298 reference statements)
1
55
1
2
Order By: Relevance
“…Among a cohort of patients in the New England Veterans Affairs Healthcare System, the use of ChEIs was associated with a modest increased risk of bradycardia (adjusted hazard ratio 1.4) [52]. In a metaanalysis of RCTs, the use of ChEIs was associated with a greater risk of syncope but not falls, fracture, or accidental injury [53]. Combined, the results of these studies highlight the importance of careful monitoring given the potential serious nature of these AEs in an elderly population.…”
Section: Safety and Tolerability Of The Cholinesterase Inhibitorsmentioning
confidence: 98%
“…Among a cohort of patients in the New England Veterans Affairs Healthcare System, the use of ChEIs was associated with a modest increased risk of bradycardia (adjusted hazard ratio 1.4) [52]. In a metaanalysis of RCTs, the use of ChEIs was associated with a greater risk of syncope but not falls, fracture, or accidental injury [53]. Combined, the results of these studies highlight the importance of careful monitoring given the potential serious nature of these AEs in an elderly population.…”
Section: Safety and Tolerability Of The Cholinesterase Inhibitorsmentioning
confidence: 98%
“…Stürze ohne ernste Verletzungsfolgen werden sowohl von älteren Menschen als auch von dem medizinischen Fachpersonal oftmals bagatellisiert, sodass präventive Maßnahmen versäumt oder zu spät eingeleitet werden, was wiederum Folgekosten für das Gesundheitswesen nach sich zieht (Zecevic, Salmoni, Speechley, & Vandervoort, 2006). Dieses Phänomen lässt die Dunkelziffer bei Stürzen zusätzlich ansteigen (Kim, Brown, Ding, Kiel, & Berry, 2011). (Weberberger, 2010) und Programme (Geißer, 2010), die im Routinealltag unter Best-PracticeGesichtspunkten durchgeführt werden (Becker, & Lenz, 2011;Lindemann, Schiele, & Tiedemann, 2005 (Becker et al, 2005;Thapa-Görder, & Voigt-Radloff, 2010).…”
Section: Folgen Für Die Gesellschaftunclassified
“…Dizziness was more common in the rivastigmine group; other trials of medications for dementia report more syncope in the treatment arms. 9 While recent studies of acetylcholinesterase inhibitors in Alzheimer's disease also support an improvement in gait variability, 10 a systematic review of studies using acetylcholinesterase therapy in PD patients showed no improvement in falls risk. 11 So should we start using rivastigmine to prevent falls in patients with PD?…”
Section: So Does Respond Herald a New Era For Falls Prevention In Parmentioning
confidence: 99%